On the sudden contact between a hot gas and a cold solid - Clark, J. F. (College of Aeronautics, 1960)
The flow induced by the sudden contact between a semi-infinite expanse of gas and a solid, initially at different temperatures, is examined on the basis of a linear continuum theory. For times large compared with the mean time between molecular collisions in the gas, the velocity and pressure disturbances are found to be concentrated around a wave front propagating out from the interface at the ambient isentropic sound speed, whilst, near to the interface, these disturbances are small and the gas temperatures are nearly equal to those predicted by the classical constant pressure heat conduction theory. The possible significance of these results in connection with reflected shock wave techniques to measure high temperature gas properties is commented upon.